PENGARUH SUHU DAN JENIS ASAM PADA HIDROLISIS PATI UBI TALAS (Colocasia esculenta L. Schott) TERHADAP KARAKTERISTIK GLUKOSA - Dewi, Ni Kadek Ariani; Hartiati, Amna; Harsojuwono, Bambang Admadi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): Desember, 2018)
The purpose of this reseach was 1) to determine the effect of temperature and acid type on hydrolysis of taro yam starch on the characteristics of glucose, 2) to determine the exact temperature and type of acid in taro starch hydrolysis which produced the best glucose characteristics. This reseach uses Randomized Block Design of factorial pattern.. The first factor is the hydrolysis temperature of taro yam starch at temperatures of 80°C, 90°C and 100°C. The second factor is the acids type of HNO 3 , H 2 SO 4 and HCl, each with 7% acid concentration. Each treatment is grouped into 2 based on the implementation time. The variables observed were reduction in sugar content, total sugar, dekstrose equivalent (DE), total dissolved solids and clarity. The results showed that the temperature treatment and acid type had a very significant effect (P<0,01) on reducing sugar content, total sugar and hydrolyzed dectrose equivalent (DE) values. Temperature treatment has a significant effect on total dissolved solids and does not significantly affect clarity. The treatment of acid types has significant effect on total dissolved solids and clarity. Temperature treatment and type of acid interact with reducing sugar content, total sugar, and DE values, do not interact with total dissolved solids and clarity. The highest yield was obtained by reducing sugar content of 3,06%, total sugar 5,64% and DE value of 54,24% in HCl at 100°C. The total dissolved solids in H2SO4 and HCl at 100°C were 5,15°Brix and the clarity of HCl at 100°C was 0,02. The best glucose characteristics at HCl was 90°C which was not significantly different from HCl at 100°C. Keywords : sugar, hydrolysis, taro yam, starch, acid, glucose